2018
DOI: 10.1590/s1413-41522018134833
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do efeito da adição de probiótico na dieta de alevinos e juvenis de tilápias-do-nilo (Oreochromis niloticus) criados em esgoto doméstico tratado

Abstract: Avaliação do efeito da adição de probiótico na dieta de alevinos e juvenis de tilápias-do-nilo (Oreochromis niloticus) criados em esgoto doméstico tratado Probiotic addition effect assessment in the diet of fingerling and juvenile Nile tilapia (Oreochromis niloticus) created in treated sewage ABSTRACT The research was conducted to evaluate the effect of using probiotic (Bacillus licheniformis, Bacillus cereus, Bacillus subitillis, yeasts and Saccharomyces cerevisiae and Saccharomyces boulardi) in diets for til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(13 reference statements)
0
6
1
Order By: Relevance
“…In a study conducted by Ferreira et al (2018), the authors supplied S. cerevisiae for tilapia reared in treated sludge and observed a mean value of 1.98 ± 0.51 mg / l of DO, which is considerably lower to the values observed in the present study. Taoka et al (2006a) reported improvements in the survival of fish and in water quality parameters such as pH, N-NH4, N-NO2 and P-PO4 when rearing Japanese sole (Paralichthys olivaceus) supplemented with several probiotics in their diet (Bacillus subtilis at 1.6 × 107 CFU g-1; Lactobacillus acidophilus at 1.2 × 108 CFU g-1; Clostridium butyricum at 2.0 × 107 CFU g-1;…”
Section: Discussioncontrasting
confidence: 94%
“…In a study conducted by Ferreira et al (2018), the authors supplied S. cerevisiae for tilapia reared in treated sludge and observed a mean value of 1.98 ± 0.51 mg / l of DO, which is considerably lower to the values observed in the present study. Taoka et al (2006a) reported improvements in the survival of fish and in water quality parameters such as pH, N-NH4, N-NO2 and P-PO4 when rearing Japanese sole (Paralichthys olivaceus) supplemented with several probiotics in their diet (Bacillus subtilis at 1.6 × 107 CFU g-1; Lactobacillus acidophilus at 1.2 × 108 CFU g-1; Clostridium butyricum at 2.0 × 107 CFU g-1;…”
Section: Discussioncontrasting
confidence: 94%
“…At this point, environmental conditions, encompassing all physical, chemical and biological parameters, allow changes in the colonization of organisms, which may or may not be beneficial and modify the vital functions for fish survival in the nursery (BRITO et al, 2019). The type of feed is a determinant of the water quality and its composition, directly influencing the seasonality of the physical, chemical and biotic parameters (FERREIRA et al, 2018).…”
Section: Sanitary Conditions and Productive Performancementioning
confidence: 99%
“…Protein-rich, nucleic acid and aminoácid desrations, when passing through catabolic processes, generate toxic residues such as ammonia, nitrites and nitrates. These nitrogen compounds have great interference with fish metabolism, organ morphophysiology since they present thresholds of toxicity and compromise basic vital functions reducing productive performance, which can decrease the rate of dissolved oxygen and the tolerance to diseases leading to high mortality (CARDOSO et al, 2016;CARVALHO et al, 2017;FERREIRA et al, 2018;MARDONES et al, 2018;MOTA et al, 2019;).…”
Section: Sanitary Conditions and Productive Performancementioning
confidence: 99%
See 2 more Smart Citations